2013
DOI: 10.1371/journal.pone.0064376
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms in the Tumor Necrosis Factor-Alpha Gene Promoter Region Alter the Risk of Psoriasis Vulgaris and Psoriatic Arthritis: A Meta-Analysis

Abstract: BackgroundIt has been confirmed that tumor necrosis factor-alpha (TNFα), a macrophage-derived pro-inflammatory cytokine, plays an important role in the pathogenesis of psoriasis vulgaris and psoriatic arthritis (PsV&PsA). In contrast, the reported association of TNFα gene promoter region single nucleotide polymorphisms (SNPs) and PsV&PsA has remained controversial. Accordingly, we performed a meta-analysis to provide new evidence that SNPs in the TNFα gene promoter region alter not only the risk of psoriasis v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
2
12
2
1
Order By: Relevance
“…The association between PsV and HLA Cw6 is relatively stronger in case of type I rather than type II psoriasis . It is not clear if the association with TNFα −238A is dependent on the disease type . In the present study, distribution of the genotype frequencies under dominant genetic model do not show any significant difference between type I and type II PsV subgroups (Table ).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The association between PsV and HLA Cw6 is relatively stronger in case of type I rather than type II psoriasis . It is not clear if the association with TNFα −238A is dependent on the disease type . In the present study, distribution of the genotype frequencies under dominant genetic model do not show any significant difference between type I and type II PsV subgroups (Table ).…”
Section: Discussioncontrasting
confidence: 67%
“…A number of studies have examined the status of TNFα gene promoter sequence polymorphism in psoriasis. Data from the various reported association studies have been subjected to at least two meta‐analyses . In both the studies, the authors found that −238A allele increased the risk of psoriasis (OR = 2.6, 2.5), while −308A reduced the risk of psoriasis (OR = 0.59, 0.57).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated a possible susceptibility role of TNF‐alpha gene polymorphisms in psoriatic arthritis but the results are conflicting. Thus, some studies have suggested a risk factor role for TNF‐alpha −238G>A and −857G>A polymorphisms, while others have failed to confirm this association . The inconsistencies in these results may reflect the small sample size of patients and controls analysed in most of the studies as well as genetic differences in the various populations.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, some studies have suggested a risk factor role for TNF-alpha À238G>A and À857G>A polymorphisms, while others have failed to confirm this association. 17,18 The inconsistencies in these results may reflect the small sample size of patients and controls analysed in most of the studies as well as genetic differences in the various populations. In particular, our data might be coincidental.…”
Section: Discussionmentioning
confidence: 99%
“…They conirmed a protective inluence of the polymorphic allele c.-308A. The polymorphic alleles of the other two frequently investigated polymorphisms also showed association with increased risk for psoriasis and PsA [42]. Another meta-analysis included nine studies with a total of 692 patients with RA.…”
Section: Pharmacogenetics Of Anti-tnfα Treatmentmentioning
confidence: 87%